William Edmond Logan's Geological Apprenticeship in Britain 1831-18421 - Torrens, H. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1999)
Summary William Logan was recently voted Canada's most important scientist. But the origin of his scientific interests has been a mystery. He attended university but not geology classes; he then became an accountant, far removed from geology. In 1833 Logan became joint manager of a copper-smelting works near Swan sea, south Wales, at that time the world copper-smelting centre. Logan's smelting operations depended on coal, a great variety of which was then avail-able here, with anthracite soon used iniron making. With such motivations, Logan enthusiastically set to work to make a comprehensive study of coal, iron and other mineral seams in the vast South Wales Coalfield. Logan's surviving notes reveal a considerable debt tothe many mineral and land survey or sand colliery viewers and engineers who were already active in the area. Such people have been written out of the history of geology, as they published little or nothing, but their part in Logan's meteoric rise as a geologist deserves recognition.